2020
DOI: 10.1002/ctm2.145
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of circulating microRNA‐125b, a risk predictor of vascular calcification, among community‐dwelling older adults*

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…A similar approach has been promoted for antineoplastic drug and more recently in antiviral drug virtual screening [ 46 ]. In addition, the process of drug repurposing for VC can be further sharpened by combining therapeutic responses with molecular markers for classifying the severity of VC [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…A similar approach has been promoted for antineoplastic drug and more recently in antiviral drug virtual screening [ 46 ]. In addition, the process of drug repurposing for VC can be further sharpened by combining therapeutic responses with molecular markers for classifying the severity of VC [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…The study protocol has been published previously ( 10 ). In brief, community-dwelling older adults (age ≥65) were prospectively recruited from health examination programs and clinics of National Taiwan University Hospital BeiHu Branch as well as Taipei municipal long-term care service centers during 2017.…”
Section: Methodsmentioning
confidence: 99%
“…Results based on this approach reportedly reduce fluctuations in data and permit cross-study comparisons. Data were then averaged with miR-125b levels calculated using the ΔΔCt method ( 10 ). If the participants' miR-125b expression levels were undetectable upon PCR cycling despite the presence of measurable Caenorhabditis elegans miR-39, we substituted their miR-125b cycle number with 40, which was the lowest detectable value specified by the cycler, followed by calculation.…”
Section: Methodsmentioning
confidence: 99%
“…Results from several studies may provide us with encouraging hints. In a prior attempt, we showed that in older adults, circulating miR-125b predicted the risk of VC, an important risk factor for frailty, in community-dwelling older adults [106,107]. A recent study showed that 2 weeks of metformin, a potential MAPK inhibitor, administration could improve myoblast functions in older adults through histone and chromatin remodeling [108].…”
Section: Mediators Of Organ Degeneration and Frailty As Emerging Diag...mentioning
confidence: 98%